Answer:
x = -5
Explanation:
4 - 2(x + 7) = 3(x + 5)
so, let's do the multiplications. remember, when two terms are multiplied, then everything of the left is multiplied with everything on the right. and a "-" flips signs.
2(x + 7) = 2x + 14
3(x + 5) = 3x + 15
so, in total
4 - 2x - 14 = 3x + 15
now, we add combinable things together, and we can also move things from one side of the equation to the other (by adding our subtracting the same thing on both sides, so that the value of the expression remains unchanged).
-2x - 10 = 3x + 15
-25 = 5x
and now, what applied to adding and subtracting also aims to multiplication and division. again, it is important to do the same thing to both sides.
-5 = x